THE USE OF COMMUNITY LANGUAGE LEARNINGMETHOD TO IMPROVE STUDENTS’ SPEAKING ACHIEVEMENT - Eko Widoyo Putro and Berlin Sibarani (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2015)
This study is aimed at improving the second grade of students’ speakingachievement by using Community Language Learning (CLL) Method. Theresearch was conducted by applying classroom action research. The subject of thisstudy was second grade of Private Senior High School (Sekolah Menengah AtasSwasta) of Dwi Tunggal Tanjung Morawa which consisted of 31 students. Tocollect the data, the instruments used were primary data (SpeakingTest) andsecondary data (interview sheet, observation sheet, field notes). It can be seenfrom the score in test I, test II and test III. In the Test I, the mean of the students’score was (64.77), in the Test II was (71.35), and the mean of the students’ scoreof the Test III was (80.90). Based on the interview, and observation sheet, itshows that the expression and excitement of the students got improved as well. Itwas found that teaching of speaking by using Community Language Learningcould significantly improve students’ speaking achievement.